The impact of fintech and banks M&A on Acquirer's performance: A strategic win or loss? - Quratulain Akhtar; Safia Nosheen (Borsa İstanbul Review, 2022)
Fintech startups symbolize a radical transformation in the financial industry that provides technology-based financial services. These newly formed business organizations use digital technologies such as computers, the internet, mobile, and data to innovate and facilitate, thus creating tough competition with formal incumbents such as banks. Banks are working on various strategies to deal with these new competitors, one of which is to buy them. So, this study focuses on mergers and acquisitions (M&As) between banks and fintech and the impact on the performance of the acquirers in the period 2010-2020. The paired-sample t-test and GMM analysis indicate a significant positive impact of fintech and bank M&As on the operating performance, liquidity, and financial leverage of banks but a negative impact on the market performance of banks in the long run. The study offers guidance for financial institutions, policy makers, and regulators in designing strategies toward new competitors in the market.
Keywords: G21; G34; O30; 330; Banks; Financial leverage; Financial technology; Liquidity; Mergers and acquisitions; Operating performance